Peningakatan Percaya Diri Menggunakan Layanan Bimbingan Kelompok Teknik Permainan Simulasi - Vista Ambar Wulan; Shinta Mayasari; Yohana Oktariana (ALIBKIN (Jurnal Bimbingan Konseling), 2019)
The problem with this research is the low of student’s self-confidence. The purpose of this research is to find out how to increase self-confidence with simulation game techniques in group counseling services of the student grade VIII Junior High School number 2 academic year 2019/2020. This research method is experiment. The research sub-subjects were 20 students who were divided into two groups, namely the control group and the experimental group. Data collection techniques using a scale of confidence. The results showed a change in student confidence after being given simulation game techniques in group counseling services This is indicated by an average increase of 8.04% and the results of data analysis using the Wilcoxon matched pairs test, obtained zcount= -2.803 ztable = 1.645 then Ho is rejected and Ha is accepted. The conclusion of the study is the simulation game techniques in group counseling services can be used to increase self-confidence in eighth graders of state junior high school 2 in the 2019/2020 school year.Masalah penelitian ini percaya diri siswa yang rendah.Tujuan penelitian untuk mengetahui peningkatan percaya diri dengan layanan bimbingan kelompok teknik permainan simulasi pada siswa kelas VIII SMPN 2 Menggala tahun pelajaran 2019/2020.Metode penelitian ini adalah Eksperiment.Subjek penelitian sebanyak 20 orang siswa yang dibagi menjadi dua kelompok yaitu kelompok kontrol dan kelompok eksperimen.Teknik pengumpulan data menggunakan Skala Percaya Diri.Hasil penelitian menunjukan adanya perubahan percaya diri siswa setelah diberikan layanan bimbingan kelompok teknik permainan simulasi. Hal ini ditunjukan dengan peningkatan rata – rata 8,04% serta hasil analisis data menggunakan uji Wilcoxon Matched Pairs Test, diperoleh = -2.803 = 1.645 maka Ho ditolak dan Ha diterima Kesimpulan penelitan adalah bimbingan kelompok teknik permainan simulasi dapat digunakan untuk meningkatkan percaya diri pada siswa kelas delapan SMPN 2 Menggala Tahun ajaran 2019/2020.Kata kunci: bimbingan dan konseling, percaya diri, teknik permainan simulasi